Optimal Conditions for Phytase Activity from Epiphytic Yeast Rhodotorula mucilaginosaZML2-31 and Their Properties for Phosphate Liberation - Chanklan, Ruthada; Jindamorakot, Sasitorn; Limtong, Savitree (Thai Journal of Science and Technology, 2022)
Epiphytic yeast ZML2-31, isolated from corn phylloplane, exhibited high activity of 46.88 U/mL extracellular and 31.25 U/mL cell bound phytase when grown on LMM supplemented with 0.5 % Na-phytate at 24 and 48 h of cultivation, respectively. The optimal pH and temperature of crude phytase were pH 4.0 and 40˚C, respectively. The residual phytase activities were more than 80% at 30-60 ˚C for 2 h. Storage stability of phytase was retained more than 75% of the initial activity after 18 days at storage temperature ≤ 30 ˚C. Addition of crude phytase to soybean and chickpea significantly enhanced inorganic phosphate liberation compared with control. Sequence analysis of D1/D2 domain of 26S rRNA gene revealed that the isolate ZML2-31 was highly related to Rhodotorula mucilaginosa with sequence identity of 99%.